Identifikasi Kontaminasi Aflatoksin pada Rempah-Rempah yang Dijual di Sentra Pasar di Kabupaten Jember - Rina Fitriana; FX. Ady Soesetijo; Erma Sulistyaningsih (Multidisciplinary Journal, 2019)
Aflatoxin is a secondary metabolite of the fungus Aspergillus flavus and Aspergillus parasiticus, the toxin is able to cause health problems in humans and animals that suffer sympthom of aflatoxin called mycotoxicosis. Both types of fungus can survive at optimally temperature of 36-38oC and moisture above 85%. Aspergillus species may contaminated some foods such as wheat, rice, corn, beans, chilies, and spices. Aflatoxin have six types, namely Aflatoxin B1, B2, G1, G2, M1 and M2. AFB1 is the most toxic among the six types of aflatoxin, it’s induce cancer by affecting Deoxyribonucleic Acid (DNA) genetic code. The aim of this research was to analyze the types and levels of aflatoxin especially spices that provided in the traditional market and supermarkets in Jember area. This research design is experimental analytic. The population is spices that belong in all of traditional markets and supermarkets in Jember area. The sample is certain spices (onion, turmeric, pepper) in the 3 traditional markets and 3 supermarkets selected by purposive sampling techniques. This research was done at Central Laboratory Agro Industry Bogor on July – September 2019. The variable of this research is aflatoxin contamination inside of spices. Aflatoxin analytic performed by High Performance Liquid Chromatography (HPLC) instruments. The results of this research showed that found some of samples that has been analyzed, the samples of pepper (C4) was taken in Supermarket ‘X’ has the highest contaminated aflatoxin B1 was 45,35 ppb and aflatoxin G1 was 50,74 ppb. Therefore, its recommended for Supermarket is to increased monitoring of temperature and humidity, especially at the storage of spices.Keyword: Aflatoxin, Fungus, Traditional Market, Spices, Supermarket